Context effects on processing widely deviant sounds in newborn infants - Háden, Gábor P.; Németh, Renáta; Török, Miklós; Drávucz, Sándor; Winkler, István (Frontiers in Psychology, 2013)
Detecting and orienting towards sounds carrying new information is a crucial feature of the human brain that supports adaptation to the environment. Rare, acoustically widely deviant sounds presented amongst frequent tones elicit large event related brain potentials (ERPs) in neonates. Here we tested whether these discriminative ERP responses reflect only the activation of fresh afferent neuronal populations (i.e., neuronal circuits not affected by the tones) or they also index the processing of contextual mismatch between the rare and the frequent sounds. In two separate experiments, we presented sleeping newborns with 150 different environmental sounds and the same number of white noise bursts. Both sounds served either as deviants in an oddball paradigm with the frequent standard stimulus a tone (Novel/Noise deviant), or as the standard stimulus with the tone as deviant (Novel/Noise standard), or they were delivered alone with the same timing as the deviants in the oddball condition (Novel/Noise alone). Whereas the ERP responses to noise–deviants elicited similar responses as the same sound presented alone, the responses elicited by environmental sounds in the corresponding conditions morphologically differed from each other. Thus whereas the ERP response to the noise sounds can be explained by the different refractory state of stimulus specific neuronal populations, the ERP response to environmental sounds indicated context sensitive processing. These results provide evidence for an innate tendency of context dependent auditory processing as well as a basis for the different developmental trajectories of processing acoustical deviance and contextual novelty.